The prevalence of male urinary incontinence in four centres: the UREPIK study. - Boyle, P; Robertson, C; Mazzetta, C; Keech, M; Hobbs, F; Fourcade, R; Kiemeney, L; Lee, C (2003)
OBJECTIVES: To report the results of the prevalence and health status associated with male urinary incontinence (UI) in a population-based, multicentre study in four countries, and to assess the epidemiology of this condition. SUBJECTS AND METHODS: A standard questionnaire asking about frequency and amount of urine loss, use of pads and stress incontinence, was used to measure the prevalence of UI among men in four countries (Boxmeer, The Netherlands; Auxerre, France; Birmingham, UK; and Seoul, Korea). Self-reported urinary leakage was also recorded, with details of visits to the doctor for the symptoms. The samples were selected randomly from population registers of men aged 40-79 years, which provided representative samples in each community. RESULTS: In all, 4979 men responded; from incontinence symptom scores, 7.3% of men aged 40-79 years in Auxerre, 16.3% in Boxmeer, 14.4% in Birmingham and 4.3% in Seoul reported mild to severe UI. On a self-reported question, 14.8% and 14.5% of men in Birmingham and Boxmeer thought that they had urinary leakage, compared with 7.5% and 7.1% of men in Auxerre and Seoul, but typically the reported incontinence was leaking drops of urine a few times a week. Of men with urinary leakage in the three European centres, 25.9% visited the doctor with this problem, compared with only 9.0% of men in Seoul. Of men in the European centres, 5.9% used pads at least occasionally, compared with only 1.6% of men in Seoul. UI was age-related and the reporting of it varied among centres, with 14.4% of men in Birmingham and 12.7% of men in Boxmeer aged 40-49 years reporting mild to severe UI, compared with 5.2% in Auxerre and 1.9% in Seoul. Among men aged 60-69 years the corresponding percentages were 13.7% in Birmingham, 22.6% in Boxmeer, 9.2% in Auxerre and 8.0% in Seoul. CONCLUSIONS: UI is more common in older men and relatively uncommon among younger men. Some men reported no problems on the symptom questionnaire but replied positively to a direct question. Surprisingly many men wear protective pads at least occasionally as a result of their problem. UI appears to be a problem for men and which remains largely untreated; this may partly be a result of cultural differences.